When Managers Change Their Tone, Analysts and Investors Change Their Tune. Issue 2 (23rd April 2020) - Druz, Marina; Petzev, Ivan; Wagner, Alexander F.; Zeckhauser, Richard J.
Abstract : The negativity of managerial word choice (managerial tone) in conference calls is a telltale indicator of a company's future. Specifically, increases in negativity–what we term "bleak tone changes"–strongly predict lower future earnings and increased uncertainty. Decreases in negativity, however, only weakly predict the opposite. To isolate the explanatory power of managerial tone, we controlled for negativity changes in the earnings press release and analysts' questions. Analysts and investors underreact when they extract value-relevant information from negativity changes. Consequently, a negativity-based trading strategy generates abnormal returns. Abstract : Disclosure: Marina Druz, Alexander Wagner, and Richard Zeckhauser declare that they have no relevant or material financial interests that relate to the research described in this article. Ivan Petzev works for an asset management firm that invests in equities globally. Authors' Note: The views expressed in this article are those of the authors and do not necessarily reflect the views of Swiss Rock Asset Management. A previous version of this article was titled "Reading Managerial Tone: How Analysts and the Market Respond to Conference Calls". Editor's Note Submitted 23 May 2019 Accepted 11 December 2019 by Stephen J. Brown